Rapid immunochromatographic test: An evolving tool for diagnosis of scrub typhus - Saha, Sabyasachi; Sanjit Kumar Patra; Mrinmoy Pathak; Jayanta Bikash Dey; Ghosh, Tapashi; Chakraborty, Sohanjan (Asian Journal of Medical Sciences, 2023)
Background: Scrub typhus is prevalent in many districts of South Bengal throughout the year where an average temperature of 20–35°C, which contributes to the spread of Leptotrombidium deliense. However, its diagnosis remains complicated by the lack of readily available and validated assays, the non-specificity of clinical symptoms on admission, and even non-availability of the pathognomonic eschar in most of the cases. Aims and Objectives: This study was carried out to evaluate the rapid immunochromatographic test (RICT) for early detection of scrub typhus for using it as an early diagnostic tool at the field level. Materials and Methods: This cross-sectional study in which 181 serum samples from clinically suspected cases (after excluding dengue, malaria, Japanese encephalitis, and typhoid fever) collected over 13 months were processed for the detection of immunoglobulin M (IgM) antibodies for scrub typhus by enzyme-linked immunosorbent assay (ELISA) and rapid test. Results: Considering IgM ELISA for scrub typhus as the gold standard, the sensitivity, specificity, positive predictive value, and negative predictive value for RICT were found to be 100%, 86.87%, 50%, and 100%, respectively. Conclusion: RICT is a simple, rapid, and reliable assay for diagnosis of scrub typhus, capable of providing accurate results quickly and is highly suitable for field deployment in remote areas with limited medical support.